Empowerment of Village Leadership in Optimizing the Potential of Local Human Resources - Kasmawanto, Zuli; Ni'mah, Khoirotun (Shof Journal of Social Impact, 2024)
This study aims to analyze the role of village leadership in optimizing the potential of local human resources (HR) in Pucangro Village. The main focus of this research is to identify human resource empowerment strategies through effective leadership and collaboration between village heads, local governments, and the private sector. The research method used is a qualitative approach with case studies, which involves interviews, observations, and document analysis to explore data on the implementation of human resource empowerment programs in villages. The results of the study show that proactive leadership from village heads plays an important role in creating an inclusive empowerment ecosystem, where the community actively participates in the planning and implementation of programs. Strong collaboration between various stakeholders is the key to success in human resource empowerment, including through relevant skills training, entrepreneurship development, and capacity building for village heads through strategic leadership training. In addition, the integration of information technology in monitoring and evaluation has also proven to be important to ensure the sustainability and effectiveness of empowerment programs. This study concludes that with the implementation of the right empowerment strategy, Pucangro Village can optimize the potential of local human resources and improve community welfare in a sustainable manner.